Dispute Settlement Patterns on The Village Chief Election at Bondowoso Regency - Fauziyah Fauziyah; Sri Praptianingsih (Rechtsidee, 2015)
Village elections (Pilkades) is a direct election procedure and mirrors implementation of democratic life in Indonesia. Article 37 and 38 of the regency Regional Regulation No. 7 of 2006 states that if the Pilkades process turns dispute, the dispute does not stop the next stage. The regency government normatively based on Article 37 guarantees the completion stage of the elections until the inauguration phase and form a team of supervisors who communicate with those who feel aggrieved to get agreement dispute resolution. Until this research is done, there is only one case submitted to the District Court, but then the plaintiffs draw their lawsuit. Dispute settlement pattern research was conducted through interviews and providing information to the bureaucrats and the judiciary in the area of dispute. The involvement of these parties is important that the results of this activity followed up by an independent institution in Pilkades dispute resolution with consideration of existing regional regulations. How To Cite: Fauziyah, F., & Praptianingsih, S. (2015). Dispute Settlement Patterns on The Village Chief Election at Bondowoso Regency. Rechtsidee, 2(1), 11-20. doi:http://dx.doi.org/10.21070/jihr.v2i1.8